El coraje de la verdad en el último Michel Foucault: su “otro modo” y su “vida otra” (1981-1984) (2021)
The objective of this article is to share with the academic community the research result based on the doctoral thesis of philosophy titled Parrhesia as heterotopia in the last Foucault: another critical and specific mode of being, (un)thinking, saying and living (2014-2018). Indeed, I attempted to outline the itinerary of the work of the last Foucault (1981-1984) as a genealogy of parrhesia (explained as ‘The courage of truth’ or veridiction), which gathers the most relevant conclusions of four years of research. Finally, I highlight the retrospective and prospective of Foucault’s parrhesia as an integral art of living from self-care, developed by its most studious authors and other contemporary trends related to this topic. Everything converges in "heterotopia" as that tetrahedral other critical and specific mode or line of flight: being, (un)thinking, saying and living, which culminates with a re-reading from the Latin American sphere as a pertinent alter-globalization proposal focused on an ethical “citizenship” —more than citizenship— in all human spheres, especially the one that concerns us most: education.